PROSES PEMBELAJARAN DARING DI MASA PANDEMI COVID 19 BAGI SISWA MADRASAH ALIYAH NEGERI 2 KABUPATEN PROBOLINGGO - Ahyar, Muhammad; sarkowi (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstract The disease Corona hit the world especially in the country of indonesia and had resulted in the decline of economic growth, especially in Indonesia, is also happening in the world of education. First learning in higher education is conducted in offline (face to face), and what happens now is learning to be done online. The research has the purpose to see how big the learning process online in the pandemic covid 19 for students of Madrasah Aliyah Negeri 2 Probolinggo. This study uses a Quantitative model with survey method. The respondents of this study amounted to 400 students. The results of this study showed that 79% of students want learning face-to-face, whereas only 1% students who want learning online, it can be concluded that online learning is continuous as long as the pandemiccis not very effective. Keywords: OnlineeLearning, Covid-19, Student